Pengembangan e-LKPD berbasis game-based learning berbantuan live worksheets pada materi pemetaan - Prista, Dynda; Sumarmi, Sumarmi; Mutia, Tuti; Utaya, Sugeng; Bernadi, Andi Irwan (Universitas Negeri Malang, 2023)
Education plays a crucial role in creating the next generation of the nation who possess quality skills and thinking and can change the world for the better. In the development of education in Indonesia in 2023, schools have adopted the 'merdeka' curriculum in their learning processes. In the era of globalization, the implementation of the 'merdeka' curriculum involves the use of technology or digital means. Concerning the outlined issues, a researcher is interested in conducting a study on the development of teaching materials, specifically an E-LKPD (Electronic Learning and Teaching Materials) based on Game-Based Learning for mapping subjects. The developmental research aims to create the E-LKPD, measure its practicality, and assess the effectiveness of student learning outcomes. The developmental model applied in this research is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). This developmental research employs both quantitative and qualitative data. For data collection techniques, the researcher uses surveys, interviews, and documentation, applying percentage techniques. The testing of the teaching material product will be carried out at Panjura Malang High School, Class X IPS. Based on evaluations from expert design validators, content expert validators, student responses, teacher responses, and the effectiveness test of student learning outcomes, it is concluded that the Game-Based Learning-based E-LKPD, aided by Live Worksheets, is highly suitable and appropriate for implementation in geography education for Class X IPS, especially for the topic of mapping. Pendidikan memiliki peran krusial dalam menciptakan penerus bangsa yang memiliki kemampuan dan pemikiran berkualitas serta bisa mengubah dunia menjadi lebih baik. Perkembangan pendidikan di Indonesia tahun 2023 sekolah sudah menggunakan kurikulum merdeka dalam proses pembelajarannya. Pada era globalisasi, pengimplementasian kurikulum merdeka menggunakan bantuan teknologi atau secara digital. Terkait dengan isu yang telah diuraikan, peneliti tertarik untuk melakukan studi pengembangan bahan ajar E-LKPD berbasis Game-Based Learning pada materi pemetaan. Penelitian pengembangan bertujuan untuk mengembangkan E-LKPD, mengukur tingkat kepraktisan, dan mengukur tingkat keefektifan hasil belajar siswa. Model pengembangan yang diterapkan pada penelitian yakni ADDIE (analisis, desain, pengembangan, implementasi, dan evaluasi). Penelitian pengembangan ini menggunakan data kuantitatif dan kualitatif. Pada teknik pengumpulan data, peneliti memakai teknik angket, wawancara, dan dokumentasi dengan menerapkan teknik persentase. Uji coba produk bahan ajar akan dilakukan di SMA Panjura Malang kelas X IPS. Berdasarkan evaluasi dari validator ahli desain, validator ahli materi, respon siswa, respon guru, dan uji keefektifan hasil belajar siswa, disimpulkan bahwa E-LKPD berbasis Game-Based Learning berbantuan Live Worksheets sangat cocok dan layak untuk diimplementasikan dalam pembelajaran geografi pada kelas X IPS, terutama pada topik pemetaan.